Containership new-building orders and freight rate shocks: A “wait and see” perspective - Michail, Nektarios A.; Melas, Konstantinos D. (My University, 2023)
This paper studies the behaviour of shipping investors following an unexpected shock in the freight rates, while accounting for costs (fuel), and the macro environment (stock prices and trade). The estimates firstly confirm the existence of a long-term relationship between the macroeconomic environment and freight rates, as well as between that and newbuilding orders. Most importantly, we find that when the source of the shock is less clear but still causes an increase in freight rates, shipping investors respond with a delay, which could last almost a year. The thinking behind this “inaction period” is rational, given that the only way to observe whether a shock is permanent or transitory is to wait it out. The above findings have important policy implications not only for shipping investors but also for countries that rely heavily on their ship-building industries.
Keywords: Alternative investments; Containerships; Impulse responses; Shipping markets